Notable Feature of MALIBNET - Raghavan, R.; Raghavan, Jayasri (DESIDOC Journal of Library & Information Technology, 2002)
This paper gives a detailed account of the objectives, structure, products, services of MALIBET, its linkages with INSDOC and the user of the Network. MALIBNET is claimed to be a model network which has become operational in a short span of four months after it is registered as a society and that too without government support except that of INSDOC. http://dx.doi.org/10.14429/dbit.16.2.3256